(untitled) (Canadian Hematology Today, 2024)
With advances in treatment for chronic myeloid leukemia (CML), the natural history of chronic phase (CP) CML has changed, with most individuals expected to live a normal life expectancy. The goal of therapy for most is to achieve a long-term deep molecular response (DMR) with the potential for medication discontinuation and treatment-free remission (TFR).1 Currently, six oral therapies have been approved for CP-CML in Canada: (1) imatinib, a first-generation tyrosine kinase inhibitor (TKI); (2) dasatinib, (3) nilotinib, and (4) bosutinib, the second-generation TKIs (2G-TKIs); (5) ponantinib, a third-generation TKI; and (6) asciminib, specifically targeting the ABL Myristoyl pocket (STAMP) inhibitor. Classically, treatment for CP-CML has consisted of front-line imatinib and switching to a 2G-TKI upon treatment resistance or intolerance. Increasingly, patients are being prescribed an upfront 2G-TKI with the goal of achieving quicker and deeper molecular remissions and a TFR.2 Challenges arise in CML when treatment with either two TKIs (imatinib + 2G-TKI) or one 2G-TKI fails, given the lack of evidence to inform clinical decision-making at this juncture. This paper aims to define TKI failure and help guide the selection of second-line treatment after failure of front-line therapy.